KONTRIBUSI PROGRAM GERAKAN PENINGKATAN PRODUKTIVITAS PANGAN BERBASIS KORPORASI DALAM PEMENUHAN KEBUTUHAN MASYARAKAT DESA HUTAN DI RPH GELON - , FITRI AJENG ANINDYA SARI; , Bowo Dwi Siswoko S.Hut., M.A, ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The population in Indonesia has increased from year to year, that influenced the rise of food needs. To fulfill that food needs, a lot of people utilized field, especially in a forest field. The government, especially State-owned Company (BUMN) established a Corporation-Based Food Production Improvement Movement Program (GP3K) to improve food sustainability and to improve a society income. This research was aimed to know how far GP3K Program contribution in fulfilling forest village society needs was. This research was conducted in RPH, Gelon, BKPH Sonde, KPH Ngawi. This research used a quantitative approach by a survey basic method. Data analysis used a qualitative data analysis to know a GP3K program enforcement process and a quantitative data analysis to know contribution obtained from the GP3K Program. Based on this research result, the contribution yielded by GP3K program covered contribution in case of food sustainability, society welfare and society income through a GP3K program harvest result. Contributions Program GP3K the respondents in RPH Gelon income that is equal to 51.33%. Prior to the program GP3K contribution corn yields by using seeds pioneer P21 at 66.9%, so the decline in revenue contribution of 15.57%.A GP3K contribution in case of food sustainability was 60% to 75%. An average/capita/year income of RPH Gelon society due to GP3K program was Rp 1,053,000 in KPP (Prayasawana Work Group)